Process Based Teaching Strategies as a Gateway to Attain Learning Outcomes and Nurture Higher Order Thinking Skills – Skill Enhancement for Teachers and Teacher Educators - Noufal; Trivedi, Jyoti; Sujata, B H; Paily , M U (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Attainment of higher order thinking skills are the backbone to achieving 21st century learning skills. Teaching - Learning of Science must essentially include the three major dimensions. I. Science as product, II. Science as process and III. Science as an attitude for daily life experiences. To attain the aim of Science Education in all its dimensions, the teaching learning process of science needs to steer its focus on Process Based Teaching. Process based teaching ensures all round learning of science, as the right application of science processes innately ensures development of right product of science and scientific attitude. We have known strategies such as discovery learning, inquiry learning, problem-based learning and project based learning for long as strategies that enhance science process skills. These processes are significant component of recently composed learning outcomes by NCERT.This paper focus on the science teacher‘s reflection on various process-based teaching strategies and its effectiveness on attaining learning outcomes and developing science process skills and higher order thinking skills. Sample of the study was upper primary teachers and DIET faculties of Tamilnadu, Karnataka and Puducherry who participated in five-day training workshop on ―Process Based Teaching and Evaluation in Science at Upper Primary Level‖ at Regional Institute of Education, Mysuru. Data was collected from the participants through pre-test and post test conducted in each session of the training programme and personal interview conducted with the participants and the feedback obtained from them. The result shows that there is a need to practice different process-based teaching strategies in normal classroom to provide scope for development of science processes amongst the next generation students. Also, the assessment of these processes, need to shift from product assessment to process assessment. Teachers need to gain skills to measure these processes by developing Activity specific Rubrics.